Improving High School Students Digital Literacy Through Digital Ethics and Skills Education (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The rapid advancement of information technology requires students to possess not only technical competencies but also strong digital ethics.  This community service program aimed to enhance high school students' digital literacy through digital ethics and skills education. The program involved 50 eleventh-grade students and was implemented using participatory methods, including training, outreach, and mentoring. The materials covered social media ethics, personal data protection, critical evaluation of digital information, and the productive use of technology. Evaluation was conducted using pre-and post-tests and behavioral observations. The results showed a significant improvement in students’ digital literacy, with average scores increasing from 56.4% to 89%. Students demonstrated better awareness of digital responsibility, misinformation, and ethical online behavior. This program effectively strengthened students’ capacity to navigate the digital environment responsibly and productively.